USE OF INSTAGRAM AS AN ALTERNATIVE MEDIA FOR INDONESIAN LANGUAGE DEVELOPMENT IN THE DIGITAL ERA - Nurhayati, Lutfi; Sopiah, Siti; Salsabila, Ririn; Ertinawati, Yuni (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to describe social media users' understanding of Indonesian language rules through quiz-based coaching on Instagram. The study employed a qualitative descriptive design, utilizing the Instagram Story polling feature on the @binakatakita account to collect data on standard and non-standard words. Fifteen quizzes were used to assess respondents' preferences. Data were obtained through documentation of poll results, non-participatory observation, and linguistic verification using the Indonesian Dictionary (KBBI) and the Indonesian Dictionary (EYD). The results showed that respondents' understanding of standard forms was inconsistent, evident in their choice of non-standard forms for words such as advice, damp, mere, and cooperation. Errors were generally influenced by spoken language habits and the use of informal language on social media. However, coaching through Instagram has been shown to positively contribute to Indonesian language popularization efforts. This study concludes that Instagram can be an adaptive, accessible, and relevant language coaching medium for the digital generation, and has the potential to improve language literacy if implemented sustainably.